Tanggung Jawab Notaris Terhadap Pembuatan Akta Otentik Melalui Sistem Elektronik - Yusmi Zam Zam Maharani; Khoidin Khoidin; Rahmadi Indra Tektona (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The explanation of Article 15 paragraph (3) provides a direction regarding the other forms of authority in question, one of the activities of which is certifying transactions with the concept of authentic creation through an electronic system. In contrast to the implementation of authentic making through an electronic system in Article 16 paragraph (1) letter m UUJN, which in essence the Notary must be physically present in front of several parties who have been determined to read and sign the deed, with formal requirements that must be met for the validity of a deed. An authentic deed is a derivative of Article 1868 of the Civil Code which is an explanation of the meaning of an Authentic Deed. So that between Article 15 paragraph (3) UUJN and Article 16 paragraph (1) letter m, there is a conflict of norms, therefore it is necessary to study further regarding the validity of an Authentic Deed based on the validity of making an authentic deed made in the concept of authentic making through an electronic system without any the physical presence of the Notary and the presenters. The focus of this jurnal research is the Notary's responsibility for making authentic deeds through an electronic system in terms of the validity of making authentic deeds, and the form of Notary's responsibility for making authentic deeds through electronic systems based on the validity of making authentic deeds.